Empowering Mulyodadi Tourism Village through assistance in bilingual promotional media and photography skills development - Ari Nurhayati; Nandy Intan Kurnia; Tyas Gita Atibrata; Andy Bayu Nugroho (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Mulyodadi is one of the villages that has been developing “agroedutourism”. Despite this potential, the village faces limited public recognition. Therefore, this community service program (PKM) was implemented to assist in the development of promotional media and to conduct a photography workshop. The program aimed to strengthen the promotional capacity, readiness, and independence of the human resources in managing tourism promotion. The creation of promotional media comprises three steps. First, collecting data on the tourism potential and selecting documentation from the village promotional team. Second, designing bilingual booklets and videos. Third, conducting a final review and revision of those media. A workshop was also conducted to optimize smartphone usage for photography purposes. The approach used in this program was a service-learning approach, which focused on building capacity, enhancing independence, and simultaneously fostering a sense of community ownership of the program. Observable changes were identified in the partner’s capability, including improved skills in photography and the availability of bilingual promotional media. These results indicate an improvement in the promotional readiness of the village and provide tangible support for continuous tourism promotion. Thus, the PKM empowers the human resources of the village by enhancing their ability to showcase their tourism potential.